2015
DOI: 10.1159/000381963
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Repair in Childhood Arterial Ischaemic Stroke with Cerebral Arteriopathy

Abstract: Background: We have previously shown that recurrent arterial ischaemic stroke (AIS) in children with cerebral arteriopathy is associated with increased circulating endothelial cells and endothelial microparticles, consistent with ongoing endothelial injury. To date, however, little is known about endothelial repair responses in childhood AIS. We examined the relationship between the number and function of circulating endothelial progenitor cells (EPC), the levels of brain-derived neurotrophic factor (BDNF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Hong et al observed, however, that the function of these elevated circulating EPCs was impaired in children with active vasculitis [ 47 ]. Similar findings were observed by Eleftheriou et al in children with arterial stroke caused by cerebral vasculitis [ 67 ].…”
Section: Other Biomarkers and Miscellaneous Vasculitides: Endothelialsupporting
confidence: 91%
“…Hong et al observed, however, that the function of these elevated circulating EPCs was impaired in children with active vasculitis [ 47 ]. Similar findings were observed by Eleftheriou et al in children with arterial stroke caused by cerebral vasculitis [ 67 ].…”
Section: Other Biomarkers and Miscellaneous Vasculitides: Endothelialsupporting
confidence: 91%
“…With the ability of differentiation and proliferation, EPCs are in a dormant state in the bone marrow under normal circumstances. Being stimulated by tissue ischemia, trauma, and other stimuli, EPCs can passively enter the peripheral blood circulation, reach the damage site of ischemic tissue, and form endothelial cells there through differentiation and proliferation to involve in endothelial repair and angiogenesis [11–13]. Particularly, EPCs has been thought to play a major role in pathophysiology of ischemic cerebral diseases [14].…”
Section: Introductionmentioning
confidence: 99%
“…7,9,17,18 Classical determinants for stroke and biomarkers reflecting endothelial injury and repair can also predict outcome. 17,19,20,21 There is also a trend for a better outcome 6 and few recurrences 17 in children treated with aspirin. In our former report of TCA, recurrence occurred in 3 of 4 children without treatment versus only one of 11 who received aspirin.…”
mentioning
confidence: 99%